Prevalence and recurrence of hamstring injuries among professional soccer players in Petaling Jaya City Football Club (FC) - Dharshinee Suresh Kumar; Ketut Tirtayasa; I Putu Adiartha Griadhi (DiscoverSys Inc., 2021)
Background: There is considerable evidence that hamstring injuries are moderate among professional soccer players and that the rates continue to remain elevated when these professional soccer players play soccer avidly. This study aims to determine the prevalence and recurrence of hamstring injuries among professional soccer players in Petaling Jaya City FC.Methods: A simple random consecutive sampling research data is the past medical record of professional soccer players from Petaling Jaya City FC Physiology Centre. They suffer from hamstring injuries directly taken from Petaling Jaya City FC. Data were analyzed using SPSS version 23 for Windows.Results: There are 30 players in Petaling Jaya City FC and 5 of them had a developing Hamstring Injury case. Out of 5 players suffering from Hamstring Injury, 2 of them had a recurrence of Hamstring Injury and all of them were males (100.00%). Most of the soccer players have played for 10-12 years (60.00%).Conclusion: The risk of getting hamstring injury increases as the age increases because of the hip flexor and the years of playing soccer excessively. In conclusion, it is safe to say that as each player's age increases, the more the possibility of the player to have a hamstring injury.